Microstrip Frequency Selective Surface For Use In Horn Filtenna - Sharipov, Zafar; Gunes, Filiz; Turk, Ahmet S.; Belen, Mehmet A.; Mahouti, Peyman; Demirel, Salih (IEEE, 2016)
This work presents design of Microstrip Frequency Selective Surface (MFSS)s to be fixed into the apertures of horn antennas for pre-filtering unwanted signals at 4GHz, 9 GHz. Thus integration of the antenna and band-pass filter is achieved into a single module so that a pre-filtering process can be carried out when signal is received by the antenna that makes the entire system be more compact and improves its performance. Furthermore since MFSS s consist of simply identical microstrip patch arrays, this constitutes a feasible solution especially when the unwanted signals are exceptionally strong compared to the desired in-band signals, which make required front-end RF filter performance be more rigorous. All the designs and analysis have been completed by the full-wave EM simulator CST using low-cost FR4 with the relative permittivity 4.4, thickness 1.58mm, loss tangent 0.0035 starting from the unit element. The paper briefly reviews the design and simulation stages compared to the measurements made by our research group and published in [8], [9] and [10]. From the measured results within 4GHz-9GHz bandwidth, it can be found that the proposed modules keep return loss characteristics of the horn antennas, meanwhile enhancing gain and beam width to effectively attenuate interference and noise signals at the out-band. Besides, this methodology implemented to design horn Filtennas to filter GSM signals at 1800 MHz for radar application. All the horn Filtennas will be presented in details in the workshop.
Keywords: Antenna; Filtenna; FSS; Horn; Engineering; Physics